Mouth Breathing and Its Impact on Atypical Swallowing: A Systematic Review and Meta-Analysis - Carmen Gómez-González; Antonio González-Mosquera; Mohammad Hamdan Alkhraisat; Eduardo Anitua (MDPI AG, 2024)
The aim of this systematic review is the assessment of the effect of mouth breathing on the prevalence of tongue thrust. The review was performed according to the PRISMA 2020 checklist guidelines, and the protocol was registered with PROSPERO (CRD42022339527). The inclusion criteria were the following: studies of clinical trials and cross-sectional and longitudinal descriptive studies that evaluate the appearance of tongue thrust in patients with mouth breathing; healthy subjects of any age, race or sex; and studies with a minimum sample group of five cases. The exclusion criteria were the following: studies with syndromic patients, articles from case reports, and letters to the editor and/or publisher. Searches were performed in electronic databases such as The National Library of Medicine (MEDLINE via PUBMED), the Cochrane Central Register of Controlled Trials, Web of Science and Scopus, including studies published until November 2023, without a language filter. The methodological quality of the included case-control studies was assessed using the Newcastle-Ottawa Scale (NOS), and the Joanna Briggs Institute (JBI) tool was used for descriptive cross-sectional studies and cross-sectional prevalence studies. A meta-analysis was conducted on studies that provided data on patients' classification according to mouth breathing (yes/no) as well as atypical swallowing (yes/no) using Review Manager 5.4. From 424 records, 12 articles were selected, and 4 were eligible for meta-analysis. It was shown that there is no consensus on the diagnostic methods used for mouth breathing and tongue thrust. The pooled risk ratio of atypical swallowing was significantly higher in the patients with mouth breathing (RR: 3.70; 95% CI: 2.06 to 6.66). These studies have several limitations, such as the heterogeneity among the individual studies in relation to the diagnostic tools and criteria for the assessment of mouth breathing and atypical swallowing. Considering the results, this systematic review shows that patients with mouth breathing presented higher risk ratios for atypical swallowing.